PENERAPAN MANAJEMEN BERBASIS AKTIVITAS UNTUK MENINGKATKAN EFISIENSI BIAYA PADA WHIZ PRIME HOTEL MEGAMASS MANADO - Kalonio, Ester R.; Poputra, Agus T.; Tirayoh, Victorina Z. (Universitas Sam Ratulangi, 2017)
The success of a company is largely determined by the accuracy of the leadership abilities in the management of the company. Cost efficiency has significance for the company in maintaining its existence in the business world. Activity Based Management is a method to achieve efficiency. The purpose of this research is to apply activity-based management method at Whiz Prime Hotel Megamass Manado by analyzing various activities in each deparment in hotel. The method used in this research is quantitative descriptive method. The results of this research is found some activities that are non value added activity in some departments in Whiz Prime Hotel Megamass Manado. However, after the implementation of activity management, the cost is not added value at each activity that does non value activity in some departments can be eliminated or reduced by Rp. 561.141.884. Thus, management can make cost reductions, so the company becomes more efficient.Keyword: Efficiency, Activity Based-Management, Non Value Added Activity